2016
DOI: 10.1177/0256090916650952
|View full text |Cite
|
Sign up to set email alerts
|

eWOM: Extant Research Review and Future Research Avenues

Abstract: Executive Summary Word-of-mouth (WOM) communication is widely accepted as a critical factor in building marketing strategies and communications. Invention of the Internet and proliferation of social media have added a new electronic dimension to traditional WOM, thereby converting it into electronicWOM (eWOM). The extant literature has focused on various aspects of eWOM such as its effect on consumer’s purchase decision process, utilization of eWOM to build brand strength and consumer loyalty, information dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 53 publications
(62 reference statements)
1
40
0
8
Order By: Relevance
“…e-WOM'un değeri literatürde iki yaklaşım kullanılarak ölçülmüştür. Birinci yaklaşım, kaç kişinin etkilendiği, ikinci yaklaşım ise nihai ve hızlı benimseyen fayda sağladığını varsaymaktadır (Mishra ve S.M.Satish, 2016).…”
Section: E-wom (Elektronik Ağızdan Ağıza İletişim) Kavramıunclassified
“…e-WOM'un değeri literatürde iki yaklaşım kullanılarak ölçülmüştür. Birinci yaklaşım, kaç kişinin etkilendiği, ikinci yaklaşım ise nihai ve hızlı benimseyen fayda sağladığını varsaymaktadır (Mishra ve S.M.Satish, 2016).…”
Section: E-wom (Elektronik Ağızdan Ağıza İletişim) Kavramıunclassified
“…Nevertheless, this impact is controversial [4]. The results differ concerning the effects of: the overall rating, the valence of the reviews, and the number of reviews [32]. Concerning the valence, it has been shown that positive fake reviews stimulate and negative fake reviews impair sales.…”
Section: Fake Reviews In 0e-commerce Marketingmentioning
confidence: 99%
“…Currently, audience sentiment is the foremost factor of eWOM about the studios [7,8]. Many researchers realize that the traditional machine learning model does not provide sufficient decision support for studios [11]. Most of the work uses latent Dirichlet allocation [12] and nonnegative matrix factorization [13] to extract the eWOM feature from audience reviews.…”
mentioning
confidence: 99%
“…However, the above works do not include any variables that capture the stock market of the studios, and our work can fill this gap in studios performance. Scholars measured the impact of eWOM through the parameters [11]. They also recognized the audience sentiment aspect of eWOM that may have a greater impact on the customer purchase decision.…”
mentioning
confidence: 99%